DETERMINATION OF THE EFFECTS OF DIFFERENT PACKAGING METHODS AND MATERIALS ON STORAGE TIME OF DRIED APPLE - KULCU, Recep (MATTER: International Journal of Science and Technology, 2018)
The aim of this study was to determine the effects of different packaging materials and packaging methods on changes in product characteristics during the storage period of dry products. In the experiments dried apples were used which were cut into cubes as dry product. In the packaging of dried apples, transparent doypack, metallized doypack, aluminum doypack, transparent plastic and paper materials are used. Dried products are placed in packing materials using special dosing machines to be 200 g each in each case. While atmospheric and vacuum packaging applications were used as packaging methods, only atmospheric packaging method was used in transparent plastic and pouch paper packages in terms of material properties. A total of 30 samples were prepared from each application. The packaged products were stored in the cabins in the SDU Agricultural Machinery and Technology Engineering Department laboratory. The temperature and humidity values in the cabin are recorded in the storage case. The products were stored for one year and one sample was opened and analyzed every fifteen day during the preservation process. The result of the study showed that the vacuum packaging is more successful and the aluminum layer material as the packaging material provides the highest protection.This study was supported by the BAP department of Süleyman Demirel University (Project Number: 4419-M1-15).